Behavioral Time Budgets and Spatial Use of Captive Forest Reindeer (Rangifer tarandus fennicus), Przewalski's Horses (Equus ferus przewalskii), and Domestic Cattle (Bos taurus) - Ljungberg, Felicia (Karlstads universitet, Fakulteten för hälsa, natur- och teknikvetenskap (from 2013), 2025)
Understanding how animals in captivity allocate their time to different behaviors and utilize various areas within their enclosures is essential for improving animal welfare and optimizing enclosure design. This study examined time budgets for different behaviors, and use of space within enclosures in three species at Nordens Ark: forest reindeer (Rangifer tarandus fennicus), Przewalski’s horses (Equus ferus przewalskii), and cattle (Bos taurus). Observations were conducted over a five-year period, and the data was analyzed to identify both species-specific and cross-species differences in behavior and spatial use. The statistical results revealed differences among species in both location use and behavior. The domesticated cattle spent significantly more time in artificial areas compared to the other breeds, reinforcing the idea that domesticated species, like cattle, may be better adapted to human-managed environments. The observational analysis highlighted some similarities among species, as sheltered areas and locations where resources such as food were placed were generally more frequently used. These patterns may be linked to resource placement and the design of the enclosures, which influence space utilization. The most prominent behavior observed was that all species spent a significant proportion of their time engaged in food-related activities. These findings highlight the importance of designing enclosures that address both species-specific and general needs for all three species. The results can not only contribute to improving animal welfare in captivity but also support conservation efforts by promoting behaviors critical for the reintroduction of threatened species, such as forest reindeer and Przewalski’s horses, into the wild. Future studies could explore the impact of relocating food resources within enclosures to assess its effect on space utilization, informing optimal enclosure design and resource distribution. Att förstå hur djur i fångenskap fördelar sin tid mellan olika beteenden och ...